ORKESTRASI DAKWAH HABIB SYEKH MELALUI MUSIK RELIGI - Siti Muntoyibah; Ahmad Nurcholis (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2021)
ABSTRACT In the current development of da’wah, it has created the character and creativity of preaschers in the vision and mission of delivering da’wah messages by utilizing social media which is often used by various groups, including youtube, instagram, twitter, facebook, and others. The influence of advances in science and technology makes information easy to obtain and dissemination of inaccurate information easily affects the mind. overcoming problems like this can be done with blessings, so that the mind is not easily deceived. One of the scholars named habib syekh used the art of religious music to follow in the footsteps of the walisongo when introducing islamic teachings to the village community without coercion. so that this becomes an interest in various ages and the atmosphere in preaching so that it doesn’t seem boring. the scholars have charismatic characteristics and different preaching to attract the attention of mad’u. the use of social media in habib syekh’s preaching is to make it easier for mad’u or social media users to easily access and share with connoisseurs of religious music. in this writing, what is meant by da;wah orchestration is the writing ofsong lyrics that contain da’wah messages by paying attention to the composition and order of music or an orchestra supported by a musical instrument. this was used by habib syekh, the bridge to invite mad’u to perform prayers. keywords: da’wah orchestration, habib syekh, religious music